Ni‐Cu‐Zn ferrites with high Curie temperature for multilayer inductors with increased operating temperatures. Issue 1 (2nd October 2020) - Reimann, Timmy; Capraro, Beate; Bartsch, Heike; Töpfer, Jörg
Abstract: We studied the sintering behavior and magnetic properties of Ni0.60‐y Cuy Zn0.42 Fe1.98 O3.99 ferrites. The shrinkage is shifted toward lower temperature with increasing Cu content y. The addition of Bi2 O3 sintering aid induces enhanced shrinkage at T  < 900°C and dense ceramics are obtained after sintering at 900°C. Such ferrites exhibit a permeability of µ  = 135‐250 depending on the composition, sintering temperature and concentration of sintering additive. Ferrites with y  = 0.20 show a high Curie temperature of T c  = 307°C. Multilayer inductors were fabricated and cofired at 900°C using ferrite tapes without and with 0.75 wt% Bi2 O3 . The compatibility of ferrite tapes with different metal pastes (Ag, AgPd, and Au) was evaluated. Ferrite tapes were also integrated between layers of low‐ k dielectric CT708 tapes and successfully cofired at 900°C. Preliminary tests indicate that the multilayer inductors can be operated up to temperatures of 250°C. This demonstrates that high‐Tc Ni‐Cu‐Zn ferrites are promising magnetic materials for inductive components for high operating temperatures.